Optimalisasi Kemampuan Perawat Community Mental Health Nursing dalam Manajemen Asuhan Keperawatan Psikososial pada Masa Pandemi COVID-19 di Kabupaten Sumedang: Optimization of Ability of Community Mental Health Nursing in Psychosocial Nursing Care Management during the COVID-19 Pandemic in Sumedang Regency - Reni Nuryani; Sri Wulan Lindasari; Popi Sopiah; Puspa Madya Nurhuda; Delli Yuliana Rahmat (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The COVID-19 pandemic has a significant impact on mental health conditions, such as experiencing psychosocial problems marked by emotional reaction’s changes, e.g. anxiety, fear of transmission, depression, stigma and social discrimination against people who are confirmed positive for COVID-19. The results of a survey in one village in Sumedang Regency show us that they have mental-emotional disorders with an average Self Reporting Questionnaire score of 14, so efforts are needed to overcome them by CMHN nurses as mental health service providers in the community. Therefore, further efforts are needed to optimize the ability of CMHN nurses in the management of psychosocial nursing care. This community service activity aims to increase the knowledge and ability of CMHN nurses in providing psychosocial nursing care to overcome psychosocial problems in the community during the COVID-19 pandemic. The methodology used is training and mentoring with an Intermediate Course Community Mental Health Nursing (IC-CMHN) model approach. Evaluation of this activity was carried by pretest and posttest also using the Behavioral Health Care Competency Survey instrument. The results obtained in the CMHN training and mentoring activities for nurses in primary health service are an increase in nurse’s knowledge which was originally worth 71 to 95 and shows changes in the level of nurse readiness mostly from low to moderate levels.